Silicone Breast Implant Rupture From Pectoralis Muscle Contraction Causing IgA Nephropathy: A Case Report - Ezmas, Mahno Noor; Norlia, Abdullah; Suraya, Aziz; Wan Md Adnan, Wan Md Hafiz; Looi, Lai Meng (Frontiers in Oncology, 2022)
A 34-year-old woman who was diagnosed with a left breast carcinoma underwent breast conserving surgery and axillary dissection. This was followed with adjuvant breast irradiation and endocrine therapy. She had a local recurrence in the breast 7 years later. She underwent a left nipple sparing mastectomy and submuscular implant reconstruction. The silicone implant ruptured during an episode of strong pectoralis muscle contraction, 5 years post implantation. MRI confirmed the rupture to be intracapsular and extracapsular. She declined implant replacement. She presented with painless haematuria 2.5 years after the rupture. A renal biopsy confirmed IgA Nephropathy.